2015
DOI: 10.1016/j.apj.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical memories for negative and positive events in war contexts

Abstract: The aim of the present study was to examine the phenomenological qualities of self-reported negative and positive memories. The study was conducted in the Gaza Strip, Palestine, and a total of 134 autobiographical memories about negative and positive events were analyzed using a version of the Phenomenological Questionnaire for Autobiographical Memory (Manzanero & López, 2007). Participants were university students, 80 percent were women and 20 percent were men. Results showed that negative memories are more c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
1
9
0
1
Order By: Relevance
“…In any case, the characteristics of memories of traumatic events may depend on cultural and/or resilience factors, as shown in a recent study assessing positive and negative memories amongst the people of the Gaza Strip (Manzanero, López, Aróztegui, & El-Astal, 2015). Thus, the same negative event could be remembered in a vivid and consistent manner or, conversely, in a fragmented manner or perhaps not at all.…”
Section: Phenomenal Qualities Of Self-reported Memoriesmentioning
confidence: 99%
“…In any case, the characteristics of memories of traumatic events may depend on cultural and/or resilience factors, as shown in a recent study assessing positive and negative memories amongst the people of the Gaza Strip (Manzanero, López, Aróztegui, & El-Astal, 2015). Thus, the same negative event could be remembered in a vivid and consistent manner or, conversely, in a fragmented manner or perhaps not at all.…”
Section: Phenomenal Qualities Of Self-reported Memoriesmentioning
confidence: 99%
“…However, it is characteristic of autobiographical memories to be recovered from different points of view, from an observer's perspective (in third person or as if it were a film) or from a field perspective (from the protagonist perspective itself). In general, this difference is not due to a pathology, dissociation, which is serious and rare, but to the normal functioning of memory (D'Argembeau, Comblain, & Van der Linden, 2003;Manzanero, López, Aróztegui, & El-Astal, 2015) and to the effect of multiple recovery that is typical in this type of memories and that also characterizes the earliest and most elaborated memories (Crawley & French, 2005).…”
Section: Amnesia Vs Poor Memorymentioning
confidence: 99%
“…In addition, it has been found that traumatic episodes are recalled more consistently over time than non-traumatic events. Core details can be remembered more clearly and accurately (Manzanero et al, 2015; Schmidt, 2004; Schönfeld and Ehlers, 2017; Segovia et al, 2017), and irrelevant details less accurately than for other autobiographical memories.…”
Section: Introductionmentioning
confidence: 99%
“…In this article, we present an exploratory case study, using data collected from a group of non-clinical participants who had been exposed to war and episodes of conflict. The research was informed by a previous study conducted in the Gaza Strip in autumn 2009 soon after the Israeli offensive known as ‘Operation Cast Lead’, in which both negative and positive low-intensity memories were evaluated in university students (Manzanero et al, 2015). The results showed that memories of negative events were more confusing, more complex, and more impaired than positive memories.…”
Section: Introductionmentioning
confidence: 99%